Differential synthesis and release of IL-18 and IL-18 Binding Protein from human platelets and their implications for HIV infection. (February 2017) - Allam, Ossama; Samarani, Suzanne; Jenabian, Mohammad-Ali; Routy, Jean-Pierre; Tremblay, Cecile; Amre, Devendra; Ahmad, Ali
Highlights: Platelets contain IL-18 transcripts but no pre-formed protein. They synthesize and release it de novo upon activation. They contain preformed IL-18BP but not its transcripts. Fresh human platelet poor plasma (PRP) contains little IL-18 in healthy individuals. Fresh PRP from HIV-infected individual contain readily detectable IL-18. Abstract: IL-18 is a pro-inflammatory cytokine belonging to the IL-1 family and is produced in the body from macrophages, epithelial and dendritic cells, keratinocytes, adrenal cortex etc. The cytokine is produced as an inactive precursor that is cleaved inside cells into its mature form by activated caspase 1, which exists as an inactive precursor in human cells and requires assembly of an inflammasomes for its activation. We show here for the first time that human platelets contain transcripts for the IL-18 gene. They synthesize the cytokine de novo, process and release it upon activation. The activation also results in the assembly of an inflammasome and activation of caspase-1. Platelets also contain the IL-18 antagonist, the IL-18-Binding Protein (IL-18BP); however, it is not synthesized in them de novo, is present in pre-made form and is released irrespective of platelet activation. IL-18 and IL-18BP co-localize to α granules inside platelets and are secreted out with different kinetics. Platelet activation contributes to plasma concentrations in healthy individuals, as their plasma samples contain abundant IL-18, while their platelet-poor plasma samples contain very little amounts of the cytokine. The plasma and PPP samples from these donors, however, contain comparable amounts of IL-18BP. Unlike healthy individuals, the platelet-poor plasma from HIV-infected individuals contains significant amounts of IL-18. Our findings have important implications for viral infections and other human diseases that are accompanied by platelet activation.